การประเมินศักยภาพการนำกากตะกอนอุตสาหกรรมมาใช้ประโยชน์ โดยการทดสอบการชะละลายโลหะหนัก - ชนัญญา หาวารี (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
To study the potential sludge utilization. Sludge were obtained from the filter press of 3 units of Industrial Estate’s central wastewater treatment plant. The composit sludge samples were constantly collected for 3 months and then analyzed. Themes of analysis covered both physical and chemical properties, including sieve analysis, pH and humidity. The Toxicity Characteristic Leaching Procedures (TCLP) was compare with Sequential Extraction Procedures, Microwave digestion method and Leachate Extraction Procedures for taken into account in the analysis as required by the Notification of the Ministry of Industry no.6 (B.E. 2540). Moreover, industrial sludge were also analyzed in aspects like organic quantity, the ratio of carbon to nitrogen, the amount of nitrogen, phosphorus, potassium, calcium and magnesium; all determined the extent to which industrial sludge could transform into fertilizer. The results of Microwave digestion method indicated that the sludge contained high concentration of copper, iron, manganese and zinc. The results of Sequential Extraction Procedures showed that during step 3 and step 4 indicated that copper, zinc, manganese and iron were extracted. The results was related to that of Microwave digestion method. The results of Sequential Extraction Procedures step 5 considering as residual which remain high concentration of heavy metals. The concentration of heavy metals obtained from the Toxicity Characteristic Leaching Procedures (TCLP) and Leachate Extraction Procedures were within the standard limit according to the Notification of the Ministry of Industry no.6 (B.E. 2540). The results implied that industrial sludges are considering as nonhazardous waste and contained 6.1-30.1% which was considering as high organic content. Other substances include carbon to nitrogen in a ratio of 30.15-17.26, phosphorus 46-29 ppm and potassium 550-1600 ppm, which was considering as very high level. The amounts of calcium and magnesium were also high; scoring at 2000-6600 ppm and 240-1500 ppm respectively. It can be conclude from these results that industrial sludges are considering as nonhazardous waste and with further study can be transformed into fertilizer particularly for use in Industrial Estate.